2012
DOI: 10.3349/ymj.2012.53.4.765
|View full text |Cite
|
Sign up to set email alerts
|

Permissive Hypotension in Extremely Low Birth Weight Infants (≤1000 gm)

Abstract: PurposeWe performed this study to evaluate the safety of permissive hypotension management in extremely low birth weight infants (ELBWIs).Materials and MethodsMedical records of all inborn ELBWIs admitted to Samsung Medical Center from January 2004 to December 2008 were reviewed retrospectively. Of a total of 261 ELBWIs, 47 (18%) required treatment for hypotension (group T), 110 (42%) remained normotensive (group N), and 104 (40%) experienced more than one episode of hypotension without treatment (group P) dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
(31 reference statements)
1
11
0
2
Order By: Relevance
“…In a retrospective cohort study by Dempsey et al, there were no significant short-term differences between ELBW infants with permissive hypotension and good perfusion and those who were normotensive (7). These findings were also shown in a study by Ahn et al, where they demonstrated that there were no significant differences in long-term neurological outcomes as evaluated by the incidence of cerebral palsy, hearing loss or developmental delay as assessed by Bayley scores (19). These studies showed worse outcomes in those infants who received treatment for hypotension; however, it is unclear whether this finding is due to the treatment itself or an underlying increased vulnerability of this treated population.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In a retrospective cohort study by Dempsey et al, there were no significant short-term differences between ELBW infants with permissive hypotension and good perfusion and those who were normotensive (7). These findings were also shown in a study by Ahn et al, where they demonstrated that there were no significant differences in long-term neurological outcomes as evaluated by the incidence of cerebral palsy, hearing loss or developmental delay as assessed by Bayley scores (19). These studies showed worse outcomes in those infants who received treatment for hypotension; however, it is unclear whether this finding is due to the treatment itself or an underlying increased vulnerability of this treated population.…”
Section: Discussionsupporting
confidence: 66%
“…We have shown that an elevated diastolic effective perfusion pressure or closing margin (diastolic ABP minus CrCP) is associated with severe IVH in very low birth weight (VLBW) infants, whereas mean ABP alone was not associated with this outcome (3). While not the primary finding in the study by Ahn et al, they also did not detect an association between blood pressure and severe IVH (19). In addition, while measured ABP does not reflect the middle cerebral artery pressure directly, it does trend to the device used for clinical decision making, which is more useful than a direct middle cerebral artery pressure measurement.…”
Section: Discussionmentioning
confidence: 65%
“…There are difficulties in extrapolating the findings of hypotensive premature infants in the neonatal intensive care unit to premature infants that become hypotensive intraoperatively. Hypotension in awake NICU patients may be a marker rather than a cause of subsequent neurologic deficits, and several studies found that isolated hypotension in very young premature infants who were otherwise well was not related to white matter neuronal damage . The authors of the ELGAN research study (extremely low gestational age newborns) were careful to point out that not finding an association between hypotension and later neurologic injury does not mean that hypotension is safe for very young and small premature infants.…”
Section: Definition Of Hypotensionmentioning
confidence: 99%
“…Aggressive hypotension therapy may lead to worse outcomes (mortality and IVH) than allowing permissive hypotension in patients with no signs of systemic hypoperfusion [24,25]. Vasopressor therapy is also controversial as some studies indicate that it is independently associated with impaired cerebral autoregulation and brain injury [4,26,27].…”
Section: Introductionmentioning
confidence: 99%